Investigations and comparisons of government open data websites through systematic functional analysis and efficient promotion approach - Iamamphai, Phassarun; Noymanee, Jeerana; San-Um, Wimol; Pasupa, Kitsuchart (2016 Management and Innovation Technology International Conference (MITicon), 2016)
This paper presents an investigation on a Thailand's open government data website and a comparison between this website and the open websites of the top 6 countries and of the top ASEAN country. The objective of this investigation and comparison was to formulate and submit recommendations that can help increase Thailand's open data ranking to the Electronic Government Agency (Public Organization) (EGA). The Thailand's open government data website has been launched recently as a part of a project called "Open Government Data" which was initiated and is operated by EGA. The website domain name is data.go.th. It comprises 730 datasets and has been built to support governance transparency. Although the website has been in operation for a few years, only a small number of users have made access to the data in the website. Therefore, this study is an attempt to promote the website to the public through systematic functional analysis and efficient promotion approaches, i.e. analyses of website features, contents, and web technologies. The results obtained from a comparison to other countries as well as the analysis of current features of Thailand's open government data website itself reveal that a higher ranking can be achieved mainly through an efficient Application Programming Interface (API) service, data preview feature, Data Management System (DMS) provided by the open source data portal software.